Rola systemu oceniania pracowników w organizacji: The role of employee appraisal in a company - Ciekanowski, Zbigniew; Ostrowska, Agnieszka (Management and Administration Journal, 2021)
In the article entitled ‘The role of employee appraisal in a company’ was described the nature, goals, rules and criteria of employee appraisal as well as the ways of how to motivate them. The appraisal of employees is the key element in the process of human resources management in a properly managed company. Appraisal as a comprehensive tool takes a central part in the system of human resources management and serves many purposes e.g. administrative, informational and motivation. Appraisal can only be effective if it takes place systematically. An effective system of appraisal is characterized by some features. It should be systemic, systematic, universal, flexible, specific, clear and easy to use. The appraisal criteria depend on the goals they are to serve and thus they are classified as qualifying, effective, behavioural and personal. A correctly conducted process of employee appraisal brings many benefits for both the company and its employees.